Dispute Resolution of Election Process in Indonesia (Case Study of Decision No.757/Pdt.G/2022/PN Jkt.Pst regarding Dispute between Prima Party and General Election Commission) - Devani Yasmin Tarisya; Labib Muttaqin (Universitas Muhammadiyah Surakarta, 2024)
This article examines the resolution of electoral process disputes in Indonesia, specifically the case study of decision No.757/Pdt.G/2022/PN Jkt.Pst regarding the dispute between the PRIMA Party and the General Election Commission (KPU). Elections are an important instrument in democracy, so the settlement of disputes that arise must be carried out fairly and in accordance with applicable regulations. This study applies a normative juridical approach through a case study method. Data is obtained from court decisions, laws and regulations, and relevant references. The analysis is conducted qualitatively to determine the legal considerations and implications of the decision. This article presents an in-depth analysis of electoral process dispute resolution in Indonesia, focusing on the case of the dispute between the PRIMA Party and the General Election Commission. This case study provides new insights into the implementation of electoral regulations and the protection of political parties' rights in the electoral process. Decision No.757/Pdt.G/2022/PN Jkt.Pst determined that the General Election Commission violated the law in determining that PRIMA Party was not eligible to participate in the election. The ruling recognized the violation of PRIMA Party's constitutional rights and ordered the Election Commission to revoke the decision. This article analyzes the legal reasoning and implications of the ruling for the conduct of fair and transparent elections. The resolution of electoral process disputes in Indonesia requires a strong system and consistent law enforcement. Decision No.757/Pdt.G/2022/PN Jkt.Pst demonstrates the importance of protecting the rights of political parties in the electoral process and the General Election Commission's compliance with applicable regulations.